(untitled) (International Conference on Computers in Education, 2013)
Campus cultural activity is usually propagandized through the Internet, pamphlets and posters. Print media draws more attention in public, but is not environmentally-friendly and economical. Similarly, Internet media is known for its prompt and rich content, but is hardly expected to arouse the interest of learners since it separates information from real-life environment. Augmented reality (AR), a promising technology of bridging virtual and real worlds, has been considered as a better choice for realizing an interactive and boundary-less mobile learning environment, or an even more advanced ubiquitous learning environment based on context-aware technology. In this paper, a novel campus touring system for cultural activity is implemented based on AR technology and smart phones which contains the built-in GPS, camera, WiFi and digital compass. Wikitude, a mobile AR implementation tool, is used for system implementation. Furthermore, two groups of students have been selected for system testing and evaluation. Experimental datum are collected and summarized via an open-ended online questionnaire. Experimental result shows that propagandizing and learning campus cultural activity through this mobile campus touring system is a more satisfying and interactive approach for college and university students.